Survival and development of Brosimum alicastrum (Moraceae) and Psidium sartorianum (Myrtaceae) seedlings differ under flooding conditions - Mendoza-Arroyo, Gustavo Enrique; Morón-Ríos, Alejandro; González-Espinosa, Mario; Alayón-Gamboa, José Armando; Macario-Mendoza, Pedro Antonio (Instituto de Ecología, A.C., 2020)
Background and Aims: Seasonal flooding in tropical forests may function as an environmental filter that affects the survival, establishment and growth of tree seedlings, with consequences for the assembly of communities. Seasonal flood and drought conditions were simulated with the objective to evaluate their effect on the survival, growth (stem length and number of leaves), as well as biomass accumulation in Brosimum alicastrum and Psidium sartorianum seedlings from the tropical forest of Campeche, Mexico. Methods: A nursery experiment was established with a completely random design with three treatments (flooding, regular irrigation and drought). For each treatment 45 seedlings were used for each species. The survival, height and number of leaves of the seedlings were measured at the beginning of the experiment and at 30 days intervals until the experiment ended at 120 days. The seedlings were then harvested and the length of the roots and the biomass accumulation were measured. Key results: The flood decreased the survival of B. alicastrum and did not change the survival of P. sartorianum. Likewise, it limited the length of the stem, the number of leaves and the biomass accumulated in both species, except for the biomass in roots of P. sartorianum. The survival of the seedlings exposed to drought and regular irrigation were not altered and showed increases in growth and accumulated biomass. Conclusions: The responses of the species contributed to understand the role of the environmental filter in the establishment of arboreal species seedlings in the lowlands of Calakmul, Campeche. Seasonal flooding in the lowlands acts as an environmental filter because it eliminates B. alicastrum seedlings, while it predominates in areas with well-drained soils, such as the hills adjacent to the low floodplains. Psidium sartorianum was well adapted to the conditions of drought and flood, as observed in its natural habitat.